Impact of Virtual Imaging Technology on Film and Television Production Education of College Students Based on Deep Learning and Internet of Things - Du, Chengye; Yu, Chijiang; Wang, Tingting; Zhang, Fengrui (Frontiers in Psychology, 2022)
More and more schools begin to design simulation technology based on Virtual Imaging Technology (VIT) and Virtual Reality (VR) in their course contents. In particular, among these technical courses, there is a need to first strengthen the Film and Television Production (FTP) education in higher institutions. This paper aims to study the impact of VRT, VR, and Internet of Things (IoT) technology on FTP courses and audience psychology in higher institutions under the era of intelligent multimedia. How to use emerging VR technology to promote students' or patients’ psychological well-being has become a new research direction, the exploration of which has a far-reaching significance for the applications of the related technologies. Firstly, the principle and applications of VR and IoT technology are described. Thereupon, the Deep Learning (DL)-based training model is used to analyze the Post-Production (PP) of VR-based Sand Table game, and the function and effect of the designed game model are discussed. Subsequently, VR-based Sand Play Therapy (SPT) is applied to mentally ill patients to obtain its therapeutic effect. The results show that the designed VR-based Sand Table game model can be used to treat mentally ill patients and alleviate their negative psychological states. Meanwhile, the Test Anxiety Scale (TAS) scores prove the significant therapeutic effect of the designed game model on patients' mental problems. Therefore, VR-based psychological SPT can be applied in the stress relief of students and the treatment of mentally ill patients, as well as alleviate their mental health problems. The research provides a new direction and some theoretical support for the application field of VR technology.